Social-psychological determinants of maternal pertussis vaccination acceptance during pregnancy among women in the Netherlands. Issue 40 (11th September 2020) - Anraad, Charlotte; Lehmann, Birthe A.; Visser, Olga; van Empelen, Pepijn; Paulussen, Theo G.W.; Ruiter, Robert A.C.; Kamp, Laura; van der Maas, Nicoline A.T.; Barug, Daantje; Ruijs, Wilhelmina L.M.; de Melker, Hester E.; Mollema, Liesbeth; et al.
Abstract: Background: Maternal Pertussis Vaccination (MPV) during pregnancy became part of the National Immunization Program in the Netherlands late 2019. This study aims to identify social-psychological factors associated with MPV acceptance among Dutch women to add to the current understanding of vaccine hesitancy worldwide, and to inform the development of communication and information campaigns about MPV. Methods: We conducted a cross-sectional study using an online survey among 611 women (174 pregnant women, 205 women who had given birth in the past two years and 232 women of 20–35 years old). The primary and secondary outcomes were vaccination intention and attitude towards MPV, respectively. Pearson's correlation and regression analyses were used to examine social-psychological and socio-demographic determinants of the outcomes. Results: Vaccination intention was most explained by attitudes towards MPV, beliefs about safety, moral norm and the belief about the effectiveness of MPV (R 2 = 0.79). Other factors associated were injunctive norm, anticipated regret of vaccinating, and decisional certainty. Attitudes towards MPV were further explained by descriptive norm, risk perceptions of side effects, and risk perceptions of the baby getting pertussis when not vaccinating, and fear of MPV and of the disease (R 2 = 0.76). Finally, pregnant women had a significantly lower intention and less positive attitude towards MPV than non-pregnant women. Conclusions: Communication about MPV should address the most important determinants of MPV intention and attitude, i.e. beliefs about safety and effectiveness and moral norms. Furthermore, such information may benefit from taking into account affective feelings of pregnant women such as anticipated regret and fear towards MPV. Further research could explore this. The timing of communication about MPV can be important as determinants of MPV acceptance may vary depending on pregnancy status.